2007
DOI: 10.1177/1049731506295623
|View full text |Cite
|
Sign up to set email alerts
|

Improving Quality of Life and Career Attitudes of Youth With Disabilities

Abstract: Improving quality of life is the primary focus as adolescents with disabilities enter adulthood. They increasingly, however, encounter difficulties transitioning into domains such as employment as these services occur near the end of their high school experience. Using an ecosystems model within a developmental approach, the program sought to improve the likelihood that adolescents will find and maintain meaningful employment as adults. The authors measured physical health, psychosocial functioning, and attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…Consistent evidence shows that people with disabilities are under-represented in the workforce despite their willingness and ability to work [2,3]. Having a disability is a key barrier to obtaining paid employment [4][5][6][7] due to a wide variety of factors such as stigma and discrimination [8,9], inadequate transportation and support, low self-esteem, inaccessible jobs and non-accommodating environments [8][9][10]. As a result of the challenges in finding employment, people with disabilities are consistently found either unemployed or working in low paying and low status jobs [6,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent evidence shows that people with disabilities are under-represented in the workforce despite their willingness and ability to work [2,3]. Having a disability is a key barrier to obtaining paid employment [4][5][6][7] due to a wide variety of factors such as stigma and discrimination [8,9], inadequate transportation and support, low self-esteem, inaccessible jobs and non-accommodating environments [8][9][10]. As a result of the challenges in finding employment, people with disabilities are consistently found either unemployed or working in low paying and low status jobs [6,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have found this age to be an appropriate time to initiate the process to most successfully affect the transition's outcome. [27][28][29] Children and youth with special health care needs and their families may benefit from discussions regarding adult transitioning that begin earlier than 12 years of age, depending on specific patient circumstances. Expectations for vocation, independent living, guardianship, reproduction, life expectancy, and other topics should be discussed at the earliest possible opportunity with parents and/or other appropriate caregivers if it is determined that the child's transition process will be different from that of children without special health care needs.…”
Section: Medical Home Interaction For Patients > 12 Years Of Agementioning
confidence: 99%
“…The control group was exposed to the following: Session 1 required the adolescent and family complete a developmental history (Barkley) survey 28 ; Session 2 consisted of a discussion on health and safety, such as wearing a helmet, exercise (Bright Futures) 29 ; and Session 3 consisted of a school and career planning interview (Adolescent Employment Readiness Center). 30 Each of the three intervention and three control sessions were immediately followed by a Satisfaction Questionnaire administered by a research assistant.…”
Section: Session 3 the Five Wishesmentioning
confidence: 99%